The Effect of Service Quality And Agency Skills on The Effectiveness of Sailing Time at Bulk Cargo Carrier - Janatha, Hafizh; Winarni, Endra; Rahayuningsih, Mahsunah (Politeknik Ilmu Pelayaran Semarang, 2024)
The length of the ship clearance process at an agency company makes a reference for each company in improving the quality of services provided and the skills of its employees. This study aims to determine the effect of service quality and skills on the effectiveness of sailing time for bulk cargo ships loaded with coal at three different agency companies on the island of Kalimantan. The method used is a quantitative approach through primary data processing on IBM SPSS (Statistical Package for the Social Science) 25 which comes from 30 respondents. The results of the research proven through the t test show that service quality and skills partially have a positive and significant influence on effectiveness. Simultaneous testing with an Fcount value of 33.755> 4.20 and a sig value of 0.000 <0.05 proves that service quality and skills together have a significant influence on effectiveness. This is supported by the coefficient of determination test which states that the service quality and skills variables have an influence of 71.4%, on the effectiveness variable, while 28.6% of effectiveness is influenced by variables outside of service quality and skills not examined by the author. The conclusion in this study is that the service quality and skills variables have a positive influence on the effectiveness variable partially and simultaneously.